Incidence of myocardial infarction among cooks and other restaurant workers in Sweden 1987-2005 - Carolina Bigert; Maria Lönn; Maria Feychting; Bengt Sjögren; Marie Lewné; Per Gustavsson (Nordic Association of Occupational Safety and Health (NOROSH), 2013)
OBJECTIVES: The aim of this study was to investigate the incidence of myocardial infarction (MI) among cooks and other restaurant workers. METHODS: A prospective cohort study comprised manual workers in the service sector in the Swedish National Census of 1985, totaling 543 497 women and 233 999 men. Restaurant workers were identified by occupational codes. Information on first time MI during 1987-2005 was obtained from nation-wide registers. We used Cox proportional hazards modeling, with separate analyses for men and women, adjusting for age, hypertension, diabetes, and socioeconomic status. RESULTS: Female cooks, restaurant and kitchen assistants, and wait staff all showed a statistically significant increase in risk of MI [hazard ratio (HR) 1.34, 95% confidence interval (95% CI) 1.21-1.48; HR 1.12, 95% CI 1.03-1.21; and HR 1.25, 95% CI 1.06-1.47, respectively]. No increased risk was found among female cold-buffet managers. Among men, there was no statistically significant increase in risk for any of these occupations. The association was not stronger for subjects working ≥5 years. Group level information on smoking habits showed a similar percentage of daily smokers among female cooks compared to female manual workers in general. CONCLUSIONS: We found an increased risk of MI among female but not male cooks, restaurant and kitchen assistants, and wait staff. The excess risk may be related to occupational factors, but the results do not clearly support the hypothesis of cooking fumes as a risk factor for MI. Job strain could be a potential explanation for the findings.